A Preliminary Study: The Urgency of STEM-Based Science Practicum Book for Secondary School - Rahmah Evita Putri; Skunda Diliarosta; Monica Prima Sari (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: The research purpose is to analyse the needs of Science Technology Engineering and Mathematic (STEM)-based science practicum books for secondary school. This is descriptive qualitative research with questionnaire and interview methods. The sample of this research were secondary school science teacher and students. The data were analysed descriptively with the results of data processing in percent (%). The results showed that 98% of secondary school science teachers did not know that STEM-based practicum activities could train 21st century students' skills and 90% of secondary school students stated that they never carried out practicum activities other than laboratory activities. The results also shows that 75% of students do not have science practicum book and only have worksheets provided when carrying out practicum activities. Furthermore, the results of the study also showed that 70% of students stated that practicum activities were not discussed deeply when they entered the class. It can be concluded that there is an urgency to develop a STEM-based science practicum book to that can practice students' 21st century skills in facing the era of the industrial revolution 4.0.Abstrak: Tujuan penelitian ini adalah untuk menganalisis kebutuhan buku praktikum IPA berbasis Science Technology Engineering and Matematic (STEM) untuk sekolah menengah. Jenis penelitian ini adalah deskriptif kualitatif dengan metode angket dan wawancara. Sampel penelitian ini adalah guru dan siswa IPA SMP. Data dianalisis secara deskriptif dengan hasil pengolahan data dalam persen (%). Hasil penelitian menunjukkan bahwa 98% guru IPA sekolah menengah tidak mengetahui bahwa kegiatan praktikum berbasis STEM dapat melatih keterampilan siswa abad 21 dan 90% siswa sekolah menengah menyatakan tidak pernah melakukan kegiatan praktikum selain kegiatan laboratorium. Hasil penelitian juga menunjukkan bahwa 75% mahasiswa tidak memiliki buku praktikum IPA dan hanya memiliki LKS yang disediakan saat melaksanakan kegiatan praktikum. Selanjutnya hasil penelitian juga menunjukkan bahwa 70% mahasiswa menyatakan bahwa kegiatan praktikum tidak dibahas secara mendalam ketika memasuki kelas. Dapat disimpulkan bahwa ada urgensi untuk mengembangkan buku praktikum sains berbasis STEM yang dapat melatih keterampilan abad 21 mahasiswa dalam menghadapi era revolusi industri 4.0.